Relevance of 3D Cholangiography and Transient Elastography to Assess Cystic Fibrosis-Associated Liver Disease?. (26th June 2016) - Lemaitre, C.; Dominique, S.; Billoud, E.; Eliezer, M.; Montialoux, H.; Quillard, M.; Riachi, G.; Koning, E.; Morisse-Pradier, H.; Savoye, G.; Savoye-Collet, C.; Goria, O.
Abstract : Background. Cystic fibrosis-associated liver disease (CFLD) is a major cause of death. The objective of our retrospective study was to describe the relevance of magnetic resonance imaging (MRI) and liver stiffness measurement (LSM) for CFLD evaluation. Methods. All cystic fibrosis adult patients evaluated by MRI and LSM were included. MR signs of portal hypertension (PHT), dysmorphia, or cholangitis were collected and LSM expressed in kPa and Metavir. Results. Of 25 patients, 52% had abnormal MRI. Median LSM was 5.7 kPa (3.4–9.9). Three patients had F2 score and one had F3 score. In patients with PHT, LSM was 7.85 kPa (3.7–9.9) compared to 5 (3.4–7.5) in others, p = 0.02 . In patients with abnormal liver function tests, 50% had increased LSM (≥F2), whereas 94% with normal tests had normal LSM (p = 0.04 ). Seven patients had abnormal MRI despite normal ultrasonography. Conclusions. MRI and LSM provide useful information on CFLD and may help to screen patients with PHT.